Development and validation of RP-HPLC method for estimation of brexpiprazole in its bulk and tablet dosage form using Quality by Design approach - Amol S. Jagdale; Nilesh S. Pendbhaje; Rupali V. Nirmal; Poonam M. Bachhav; Dayandeo B. Sumbre (SpringerOpen, 2021)
Abstract Background A new, sensitive, suitable, clear, accurate, and robust reversed-phase high-performance liquid chromatography (RP-HPLC) method for the determination of brexpiprazole in bulk drug and tablet formulation was developed and validated in this research. Surface methodology was used to optimize the data, with a three-level Box-Behnken design. Methanol concentration in the mobile phase, flow rate, and pH were chosen as the three variables. The separation was performed using an HPLC method with a UV detector and Openlab EZchrom program, as well as a Water spherisorb C18 column (100 mm × 4.6; 5m). Acetonitrile was pumped at a flow rate of 1.0 mL/min with a 10 mM phosphate buffer balanced to a pH of 2.50.05 by diluted OPA (65:35% v/v) and detected at 216 nm. Result The developed RP-HPLC method yielded a suitable retention time for brexpiprazole of 4.22 min, which was optimized using the Design Expert-12 software. The linearity of the established method was verified with a correlation coefficient (r2) of 0.999 over the concentration range of 5.05-75.75 g/mL. For API and formulation, the percent assay was 99.46% and 100.91%, respectively. The percentage RSD for the method's precision was found to be less than 2.0%. The percentage recoveries were discovered to be between 99.38 and 101.07%. 0.64 μg/mL and 1.95 μg/mL were found to be the LOD and LOQ, respectively. Conclusion The developed and validated RP-HPLC system takes less time and can be used in the industry for routine quality control/analysis of bulk drug and marketed brexpiprazole products. Graphical abstract